Road safety legal compliance among Malaysian motorcyclists - Siti Nur Suhanna, H.; Mohd Najib, Y. (Penerbit Universiti Malaysia Pahang, 2022)
With the ever increasing popularity of motorcycles as a mode of transport in Malaysia and several other countries in Southeast Asia, numerous of legislation, enforcement and other legal compliance are available to improve their effectiveness toward motorcyclists. The awareness level among motorcyclist toward legal compliance is very important to the motorcyclist to check and balance their knowledge and attitude toward road safety. The main objective on this study is to measure the level of compliance among motorcyclist towards Road Safety Legislations. Furthermore, the common errors done by motorcyclist during riding, and also legal compliance related to motorcycle are discussed in this study. A descriptive and cross sectional study was used to identify the level of awareness among motorcyclist towards legal compliance by using observation and a set of questionnaire. The result from the study revealed that knowledge and attitude among motorcyclists were good toward legal compliance of Road Safety regulations.